A complete guide to technical trading tactics : how to profit using pivot points, candlesticks & other indicators - Person, John L. (John Wiley & Sons, 2004)
A thorough trading guide from a professional trader. The Complete Guide to Technical Trading Tactics can help the new individual investor understand the mechanics of the markets. Filled with in-depth insights and practical advice, this book details what it takes to trade and shows readers how they can broaden their horizons by investing in the futures and options markets.